Analysis of demand and influencing factors for smart senior care among older adults in underdeveloped regions of western China: a case study of Lanzhou - Wang, Yunhua; Zeng, Hongyu; Lv, Fengli; Wang, Jiancheng (Frontiers in Public Health, 2024)
Introduction With the rapid development of artificial intelligence and Internet-of-Things technology, internal support systems among families are gradually weakening, which can no longer satisfy the current demands of older adults. In this context, smart senior care has become a new development direction. However, existing studies on the demand for smart senior care are primarily concentrated in economically developed provinces and mega-cities in eastern China; their research results or conclusions may not apply to underdeveloped areas in the Western region. Therefore, our study selects Lanzhou as a representative city in an underdeveloped western region to investigate the demand of older adults for smart senior care and analyze the influencing factors. Methods This cross-sectional study included 4,815 older adults from Lanzhou, China. A structured questionnaire was designed to investigate the demands of the older adults for smart senior care and analyze thie influencing factors. The Chi-square test was used for single factor analysis of each variable. The logistic regression model included the statistically significant variables to analyze factors influencing older adults’ demand for smart senior care. A significance level of p < 0.05 was considered statistically significant. Results Among the surveyed older adults, 1,625 (33.75%) expressed a demand for smart senior care. The finding indicated that participants’ age, level of education, marital status, monthly income, number of children, type of endowment insurance, and knowledge of smart senior care were significantly associated with their demands for smart senior care (p < 0.05). Notably, medical care emerged as the smart senior care service with the highest demand rate (79.45%). Conclusion In Lanzhou, older adults show a low level of knowledge but a high demand for smart senior care. Their demand is influenced by personal, family, health conditions, senior care security, and other factors. To advance smart senior care, government departments should accelerate the improvement of the laws and regulations on smart senior care while vigorously enhancing the service’s publicity to raise knowledge about it. Additionally, the service contents for smart senior care should be expanded to meet the diversified demands of older adults.